FIRST EXPERIENCE OF CYMEVEN IN THE COMBINED THERAPY OF RHEUMATOID ARTHRITIS - R M Balabanova; T S Salnikova (Научно-практическая ревматология, 2001)
Ummary Objective. To reveal J'reguency of accompaning virus infection and possibility to use antivirus therapy together in therapy RA. Material. 40 patients with RA at the age of 17-45 were studied. The duration of disease was not more than 6 months; patients had 2-3 degrees of activity. Every one had a positive rheumatoid factor. Results. 78,2% of the examined patients connected the beginning of the illness with virus infection they have had. The most difficalt variant of RA course and uneffectiveness of basic therapy were registerd among the patients with combination HSV and CMV infection. Inclusion of Cymevene in complex therapy RA has exerted positive influence on clinical-laboratory, signs stregthened effect of basic therapy. Conclusion. The most difficult variant of RA course was registered among the patients with virus infection. Inclusion of antivirus drugs had a positive influence on effectiveness of basic therapy.